PENGELOLAAN EKOSISTEM LAMUN DALAM MENDUKUNG KEBERLANJUTAN DUGONG - Wawo, Mintje (Balobe: Jurnal Pengabdian Masyarakat, 2024)
Seagrass is one of the three important ecosystems in coastal areas. Seagrass usually forms large fields under the water column and still gets sunlight so that it becomes high primary production. Seagrass ecosystem and the marine biota within it are utilized to improve the welfare of community living in the coastal areas. The impact of these activities causes a decrease in the quality and quantity of seagrass ecosystem, resulting in disruption of the balance of aquatic ecosystems and reduced water productivity as well as the survival of marine biota such as dugongs which is vulnerable to extinct. Therefore, to preserve the seagrass ecosystem, it is necessary to introduce to the students about the importance of seagrass ecosystems and awareness for the environment from an early age. This community service activity was conducted at SMA Negeri 39 in Waai Village, Central Maluku using the lecture/discussion method. The results of the activity can be seen from the questions they asked during the discussion/question and answer session and when giving the pre and post-test. This shows that the service activities carried out received a positive response even though they were simple in implementation. This community service activity is expected to increase knowledge and awareness about seagrass ecosystems and marine biota, especially dugong, and to change people's mindset, behavior and love for coastal areas from an early age.